Work-Related Musculoskeletal Disorders in Iranian Dentists: A Systematic Review and Meta-analysis - Hamid Reza ZakerJafari; Mohammad Hossein YektaKooshali (Elsevier, 2018)
Background: Work-related musculoskeletal disorders are the most important problems among professions particularly, dentists. This study was conducted to determine the prevalence of musculoskeletal disorders in various parts of the body in Iranian dentists by using systematic review and meta-analysis. Methods: This systematic review and meta-analysis was based on preferred reporting items for systematic reviews and meta-analyses (PRISMA) guidelines and searching in national databases such as SID, Magiran, Irandoc, IranMedex, and Medlib, and international databases such as MedLine, Web of Sciences, Scopus, PubMed, ScienceDirect, Cochrane, Embase, Springer, Wiley Online Library, Ebsco, CEBM, and Google Scholar search engine which were published by January 1, 2017. Researched keywords were in Persian and their standard English equivalents were in accordance with their MeSH. The obtained documents were analyzed using Comprehensive Meta-analysis version 2. Results: According to 23 studies through 2,531 Iranian dentists which took part in this study, prevalence of skeletal disorders in Iranian dentists has been 17.6% [confidence interval (CI) 95%:11.7-25.5] in knees, 33.2% (CI 95%:24.1-43.8) in shoulders, 33.4% (CI 95%: 26.8-40.8) in the thorax, 51.9% (CI 95%:46.7-57.2) in necks, 33.7% (CI 95%:28.2-39.6) in wrists/hands, 12.9% (CI 95%:7.7-20.6) in elbows, 37.3% (CI 95%: 31.5-43.5) in lower back, 11.9% (CI 95%:8.7-16.1) in thighs, 12.9% (CI 95%:3.8-36) in the foot, and 10.5% (CI 95%:7-15.4) in legs. Conclusion: Considering the high prevalence of musculoskeletal disorders in Iranian dentists, ergonomics should be included as a lesson in preclinic and also, reeducation courses for ergonomics basics should be executed for graduate dentists. Keywords: discomforts, Iran, musculoskeletal diseases, occupational dentists, prevalence